2007
DOI: 10.1364/ao.46.005347
|View full text |Cite
|
Sign up to set email alerts
|

Optical temperature sensing based on the Goos-Hänchen effect

Abstract: The possibility of constructing an optical sensor for temperature monitoring based on the Goos-Hänchen (GH) effect is explored using a theoretical model. This model considers the lateral shift of the incident beam upon reflection from a metal-dielectric interface, with the shift becoming a function of temperature due mainly to the temperature dependence of the optical properties of the metal. It is found that such a sensor can be most effective by using long wavelength p-polarized incident light at almost graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Due to the extremely sharp resonance in the ATR reflectivity spectrum associated with the LRSP excitation, it has been exploited in the literature to achieve ultra-high sensitivity in various sensor applications [40,41] by monitoring the change in reflectivity and phase across the very sharp resonance reflectance dip. Here we provide in the following an alternative scheme for temperature sensing by monitoring the GH shifts associated with the SP and LRSP excitations, by demonstrating the strong temperature dependence of these shifts via numerical simulations, and by comparing them with those observed previously from a bare metallic surface which was then applied to temperature sensing with modest sensitivity [26]. We shall also see that the high temperature sensitivities for both the SP-and LRSP-induced shifts are of comparable magnitudes in general.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Due to the extremely sharp resonance in the ATR reflectivity spectrum associated with the LRSP excitation, it has been exploited in the literature to achieve ultra-high sensitivity in various sensor applications [40,41] by monitoring the change in reflectivity and phase across the very sharp resonance reflectance dip. Here we provide in the following an alternative scheme for temperature sensing by monitoring the GH shifts associated with the SP and LRSP excitations, by demonstrating the strong temperature dependence of these shifts via numerical simulations, and by comparing them with those observed previously from a bare metallic surface which was then applied to temperature sensing with modest sensitivity [26]. We shall also see that the high temperature sensitivities for both the SP-and LRSP-induced shifts are of comparable magnitudes in general.…”
Section: Introductionmentioning
confidence: 57%
“…Applications of these GH shifts have been explored from time to time for the last several decades: from designing new sensing technologies [26] to slowing down light by the negative shifts [27]. However, the generally small magnitudes in these shifts have limited such applications mostly to the laboratories; and this has motivated many researchers in recent years to explore new optical structures which will lead to significantly large GH shifts (both positive and negative shifts).…”
Section: Introductionmentioning
confidence: 99%
“…This huge Goos-Hänchen effect driven by the BSW gives a way to new types of planar photonic devices, as spectrally and angularly dependent spatial modulators of the light beam that can be easily controlled and able to move the beam hundreds of microns. The optical sensors using the Goos-Hänchen effect [42,43] also can be upgraded with BSWs substituting the surface plasmons.…”
Section: The Goos-hänchen Effect Driven By the Bswmentioning
confidence: 99%
“…Goos-Hänchen (GH) effect, which refers to the lateral shift deviated from the position predicted by geometrical optics when a light beam is totally reflected at a dielectric interface [1,2], has received much attention because of its potential applications in the design of optical devices such as optical waveguide switch [3], optical sensors [4], etc. This phenomenon was theoretically explained by Artmann using stationary phase method [5], and was observed in experiments [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Later, electric control of the lateral shifts for the reflected and transmitted beams was realized due to the electro-optic effects [29,30]. Chen et al reported the possibility of constructing an optical sensor for temperature monitoring based on the Goos-Hänchen effect [4].…”
Section: Introductionmentioning
confidence: 99%